GROWTH PERFORMANCE OF WEST AFRICAN DWARF SHEEP FED DIETS SUPPLEMENTED WITH FOSSIL SHELL FLOUR (2016)
Inorganic feed additives are commonly used in small ruminant production to promote growth. However, the problem of bioaccumulation of chemical residues in animals fed inorganic feed additives has necessitated the search for organic alternatives such as Fossil Shell Flour (FSF). There is dearth of information on the use of fossil shell flour as a feed additive in the diet of small ruminants. Hence, growth performance of West African Dwarf (WAD) sheep fed diets supplemented with FSF were investigated. Sixteen WAD rams (18.5±1.05 kg) were allotted to four treatments: Tl (0% FSF), T2 (2% FSF), T3 (4% FSF) and T4 (6% FSF) in a twelve-week growth study. Daily Weight Gain (DWG, kg), Feed Intake (FI, kg/day) and Feed Conversion Ratio (FCR) were measured. Nutrient digestibility was determined using standard procedures. In vitro gas production characteristics, Organic Matter Digestibility (OMD), metabolisable energy (MJ/kg) and Short Chain Fatty Acid (SCFA, µmol/mL) of the feed were determined at three hours interval for ninety-six hours. Synchronized sixteen primiparous WAD ewes (25.75±1.60 kg) mated with proven rams were randomly allotted to the experimental diets. Dams and their lambs were weighed weekly for 13 weeks. Gestation Length (GL, days), Dry Matter Intake (DMI, g/day), Total Weight Change During Pregnancy (TWCDP, kg), Weight Change During Lactation (WCDL, kg) as well as Lamb Weaning Weight (LWW, kg), Pre-Weaning Mortality (PWM, %) and Twin Survival Rate (TSR, %) were monitored. Data were analysed using descriptive statistics and ANOVA at α0.05. The DWG for rams on T3 (0.20¬±0.04) was significantly higher than T4 (0.11±0.01) but similar to T1 (0.15±0.01) and T2 (0.19±0.03), while FCR was higher for those on T4 (9.90±1.03) than those on T3 (4.50 ±0.69). The FI ranged from 0.90±0.16 (T3) to 1.09±0.11 (T4). Crude protein digestibility was higher in sheep on T3 (82.8±1.6%) than T2 (77.8±1.2%) but similar to T1 (81.7±1.4%) and T4 (81.9±1.5%), while ash digestibility ranged from 63.6±1.2% (T1) to 72.5±1.6% (T2). The OMD ranged from 65±1.6% (T4) to 53.4±1.8% (T1) at 72 hours and from 62.2±1.4% (T2) to 54.5±1.1% (T1) at 96 hours however, no significant difference was observed among the dietary treatments for metabolisable energy and SCFA. The GL ranged from 148.50±0.13 (T1) to 152.72±0.21 (T4), while the DMI for the ewes on T2 (893.29±0.14) was significantly higher than those on T3 (860.74±0.17) however, T3 (860.74±0.17) and T4 (866.63±0.12) were not significantly different. The TWCDP ranged from 10.25±0.41 (T3) to 15.68±0.56 (T1). The WCDL significantly decreased for sheep on T4 (-2.75±0.16) than those on T1 (-1.09±0.13), T2 (-0.75±0.12) and T3 (-1.50±0.15) however, T1 (-1.09±0.13) and T2 (-0.75±0.12) were not significantly different. The LWW ranged from 8.10±0.12 (T4) to 9.23±0.18 (T3), PWM from 20±0.1 (T4) to 33.3±0.2 (T1) and TSR from 50±0.18 (T4) to 100±1.05 (T2 and T3). Inclusion of 2.0% fossil shell flour in the diet of West African dwarf sheep improved dry matter intake and reduced weight loss during lactation, while the inclusion at 4.0% enhanced the daily weight gain